Papillary and muscle invasive bladder tumors with distinct genomic stability profiles have different DNA repair fidelity and KU DNA-binding activities. - Bentley, J; L'Hôte, C; Platt, F; Hurst, C; Lowery, J; Taylor, C; Sak, S; Harnden, P; Knowles, M; Kiltie, A (2009)
Low-grade noninvasive papillary bladder tumors are genetically stable whereas muscle invasive bladder tumors display high levels of chromosomal aberrations. As cells deficient for nonhomologous end-joining (NHEJ) pathway components display increased genomic instability, we sought to determine the NHEJ repair characteristics of bladder tumors and correlate this with tumor stage and grade. A panel of 13 human bladder tumors of defined stage and grade were investigated for chromosomal aberrations by comparative genomic hybridization and for NHEJ repair fidelity and function. Repair assays were conducted with extracts made directly from bladder tumor specimens to avoid culture-induced phenotypic alterations and selection bias as only a minority of bladder tumors grow in culture. Four noninvasive bladder tumors (pTaG2), which were genetically stable, repaired a partially incompatible double-strand break (DSB) by NHEJ-dependent annealing of termini and fill-in of overhangs with minimal loss of nucleotides. In contrast, four muscle invasive bladder cancers (pT2-3G3), which displayed gross chromosomal rearrangements, repaired DSBs in an error-prone manner involving extensive resection and microhomology association. Four minimally invasive bladder cancers (pT1G3) had characteristics of both repair types. Error-prone repair in bladder tumors correlated with reduced KU DNA-binding and loss of TP53 function. In conclusion, there were distinct differences in DSB repair between noninvasive papillary tumors and higher stage/grade invasive cancers. End-joining fidelity correlated with stage and was increasingly error-prone as tumors became more invasive and KU binding activity reduced; these changes may underlie the different genomic profiles of these tumors.